2011
DOI: 10.1590/s0100-736x2011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco associados à infecção por Toxoplasma gondii em granjas suinícolas tecnificadas no Estado de Alagoas

Abstract: Objetivou-se com este estudo calcular a prevalência e identificar os fatores de risco associados à infecção por Toxoplasma gondii em suínos criados em granjas tecnificadas no Estado de Alagoas, Brasil. Para compor a amostra do estudo de prevalência foram utilizados 342 suínos, sendo 312 matrizes e 30 varrões, oriundos de sete granjas de ciclo completo e distribuídas em cinco municípios do Estado de Alagoas. O exame sorológico para a pesquisa de anticorpos anti-Toxoplasma gondii foi realizado através da técnica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
4
1
1
Order By: Relevance
“…However, the occurrence of toxoplasmosis in pigs found in this study was higher than those observed in previous studies: 36.2% in Paraíba (Azevedo et al 2010); 26.9% in Alagoas (Valença et al 2011); 18.2% in Bahia (Bezerra et al 2009); 12.8% in Mato Grosso (Muraro et al 2010); 12.6% in Paraná (Santos et al 2015) and 12.5% in Pernambuco (Fernandes et al 2012). But was lower than observed in Rio de Janeiro (65.8%; Bonna et al 2006) and Rio Grande do Sul (86.0%; Silva et al 2003).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…However, the occurrence of toxoplasmosis in pigs found in this study was higher than those observed in previous studies: 36.2% in Paraíba (Azevedo et al 2010); 26.9% in Alagoas (Valença et al 2011); 18.2% in Bahia (Bezerra et al 2009); 12.8% in Mato Grosso (Muraro et al 2010); 12.6% in Paraná (Santos et al 2015) and 12.5% in Pernambuco (Fernandes et al 2012). But was lower than observed in Rio de Janeiro (65.8%; Bonna et al 2006) and Rio Grande do Sul (86.0%; Silva et al 2003).…”
Section: Discussioncontrasting
confidence: 85%
“…The presence of rodents on pig farms was described by Valença et al (2011) as a risk factor not only because rats attract cats, which could eliminate oocysts in their feces and contaminate the environment, but also because these animals could be infected by ingesting rodents with tissue cysts. Although the presence of rodents did not represent risk for pig infection in the present study (OR=0.6, CI 95%, 0.40-0.90), the epidemiological questionnaire revealed that 41.7% of the animals from the farm with rodent presence were positive for T. gondii, which suggests a participation of the rodents in pig infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, a análise estatística realizada na amostra em estudo não evidenciou associação de riscos significativos quanto o acesso de gatos em depósitos, uma vez que o intervalo de confiança não foi significativo. Este dado está de acordo com outros trabalhos, como Valença et al (2011), em granjas de suínos e Pereira et al (2012), em propriedades de ovinos e caprinos, os quais também demonstraram que não houve esta associação à infecção pelo T. gondii acesso de gatos em locais de armazenamento de alimentos. Conforme Cademartori et al (2008), a maioria dos estudos epidemiológicos já realizados não são uniformes quanto à associação entre a infecção por T. gondii e o convívio com gatos, relatando que também não foi constatada essa associação em trabalho realizado com gestantes em Pelotas/RS.…”
Section: Discussionunclassified
“…In immunocompromised patients, such as those with HIV/AIDS, infection can cause life-threatening encephalitis and be fatal if not recognized and treated soon after infection (Montoya and Liesenfeld, 2004). Infection with T. gondii in animals has resulted in economic losses to livestock or animal husbandry (Caldeira et al, 2011; Valença et al, 2011). Infection occurs through ingestion of food or water contaminated with oocysts and eating undercooked or raw meat containing tissue cysts (Hill and Dubey, 2013).…”
Section: Introductionmentioning
confidence: 99%